Ciri Khas Pondok Pesantren Darul Amanah Desa Ngadiwarno Kecamatan Sukorejo Kabupaten Kendal Provinsi Jawa Tengah - Ana Rohmatul Wahdah; Andiani Jelita Putri Kurniawan (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
Darul Amanah Islamic Boarding School is one of the hundreds of boarding schools for Gontor alumni in Central Java. This cottage is in Ngadiwarno Village, Sukorejo District, Kendal Regency, Central Java. Darul Amanah Islamic Boarding School was established in 1990 under the leadership of Father KH. Mas'ud Abdul Qodir and assisted by his two sons, named H. Muhammad Adib Lc., MA and H. Muhammad Fatwa S.Pd.I. This Islamic boarding school was called Gontor Alumni, because the leaders of the Islamic boarding school or Islamic boarding school caretakers were alumni of Gontor alumni at that time, not to forget that the Darul Amanah Islamic Boarding School also had 5 essential souls that every Darul Amanah santri wanted to have, namely a soul of sincerity, a spirit of independence, a spirit of simplicity, the spirit of ukhuwah Islamiyah and the spirit of freedom.